An association of knowledge and misconceptions with health seeking behaviour for dog bite: a cross-sectional study in Ahmedabad - Jakasania, Arjunkumar Hardas; Mansuri, Farzana Mustufabhai; Dixit, Grishma Trambaklal (International Journal Of Community Medicine And Public Health, 2017)
Background: Rabies is a deadly zoonotic disease and most often transmitted to humans through a dog bite. It is 100% fatal yet 100% preventable with timely and appropriate Post Exposure treatment. There are myths associated with a dog bite and rabies and which might affect the health seeking behaviour. The objectives of the study were to assess the knowledge and misconceptions regarding dog-bite and rabies in primary school teachers and to know the association of misconceptions with health seeking behaviour for dog-bite in the study group. Methods: A cross-sectional study was conducted among 196 teachers of municipality and self-finance primary schools in Ahmedabad city. A pre-tested and pre-designed questionnaire was used to collect data of knowledge & attitude regarding dog-bite/rabies. Results: Out of 196 teachers, 118 teachers will not take ARV injection after bite of a normal looking dog. Many of them have a misconception about ARV injection. 128 teachers will discontinue ARV after a dog bite if any symptoms of Rabies will not develop within 10 days after starting ARV. There is an association found between knowledge regarding rabies and treatment seeking behaviour which was found statistically significant. Conclusions: There is a serious gap in knowledge regarding Rabies in primary school teachers and misconceptions regarding rabies are rampant in most of them. The misconceptions regarding rabies and dog bite found to be affecting the treatment seeking behaviour after dog bite which leads to low compliance to ARV.